Factors Affecting The Financial Performance of Local Government An-tecedents in Indonesia - Metalia Mega; Suhendro Saring (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2022)
This research aims to determine the effects of provincial revenue of the Audit Board of Indonesia (Badan Pemeriksa Keuangan, BPK) on the financial performance of district and city governments. Furthermore, financial performance is measured by four criteria: independence, economy, efficiency, and effectiveness. Multiple regression with panel data and fixed models were used by the 15 district and city governments from 2015 to 2019. The results showed that size of local government and the audit opinion of BPK have a positive effect, while the intergovernmental revenues does not have a positive effect.